2002
DOI: 10.1080/01926230252929882
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Changes in Rats Given Daily Subcutaneous Injections of Recombinant Human Parathyroid Hormone (1-34) for 2 Years and Relevance to Human Safety

Abstract: Fischer 344 rats (60/sex/group) were given daily subcutaneou s injections of recombinan t human parathyroi d hormone (PTH)(1-34) for 2 years at doses of 0, 5, 30, or 75 l g/kg. Treatment caused substantial increases in bone mass consistent with the known pharmacologi c effects of once-daily administration. As determined by quantitative computed tomography (QCT) and histomorphometr y, bone mass was markedly increased. Substantial new bone formation resulted in a large decrease in marrow space accompanie d by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
423
1
19

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 611 publications
(460 citation statements)
references
References 44 publications
14
423
1
19
Order By: Relevance
“…(2) This study reported a 26% incidence of osteosarcoma in 360 Fisher 344 rats that received teriparatide at doses of 5, 30, or 75 mg/kg/day, beginning at 6 to 8 weeks of age. (2) The occurrence of osteosarcoma was dose-dependent, with the first histopathological and clinical detection occurring after 13 and 17 months, respectively. (2) Other bone neoplasms, including osteomas, osteoblastomas, and focal osteoblast hyperplasia, were found.…”
Section: Osteosarcomamentioning
confidence: 89%
See 4 more Smart Citations
“…(2) This study reported a 26% incidence of osteosarcoma in 360 Fisher 344 rats that received teriparatide at doses of 5, 30, or 75 mg/kg/day, beginning at 6 to 8 weeks of age. (2) The occurrence of osteosarcoma was dose-dependent, with the first histopathological and clinical detection occurring after 13 and 17 months, respectively. (2) Other bone neoplasms, including osteomas, osteoblastomas, and focal osteoblast hyperplasia, were found.…”
Section: Osteosarcomamentioning
confidence: 89%
“…The effects on rats was doseand duration-dependent, with rats being treated for approximately 80% of their lifetime and at doses three to 58 times the currently approved human dose. (2) Similar toxicity was seen for PTH (3) Given the clear-cut efficacy data when the results of the abbreviated clinical trial results for teriparatide were analyzed, the FDA and equivalent other agencies in Europe and elsewhere granted approval of teriparatide with the stipulations that it should be used for no longer than 2 years. In the United States, the drug carries a ''black box warning'' and contraindicates its use in patients with existing risk factors for osteosarcoma, including Paget's disease of bone, prior skeletal radiation, and children with open epiphyses.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations